On the properties of blocks of terms of the series $\sum \cfrac1k \sin kx$ - Telyakovskii, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We investigate the decomposability of the series $\sum \cfrac1k \sin kx$ into blocks such that the sum of the series formed of themoduli of these blocks belongs to the spaces $L^p[0, \pi]$ or the spaces $L^p[0, \pi]$ with weight $x^{-\gamma},\quad \gamma < 1$.